New quinone-based electrode additives electrochemically polymerized on activated carbon electrodes for improved pseudocapacitance - Lee, Kyuchul; Hwang, Jihyun; Park, Jeong Ho; Park, Jongwook; Lee, Kangwon; Ko, Jang Myoun (Macromolecular research, 2023)
Three quinone-based derivatives (HBU680, HBU888, and HBU889) are synthesized and separately mixed with activated carbon (AC) and electropolymerized to form a homogeneous composite electrode. The electrochemical properties of the composite electrodes are studied. The electrochemical properties are mainly characterized by PhQ-PhQH2 and Q-QH2 redox transitions. The composite electrodes show specific capacitance of 176 F/g, 262 F/g, and 145 F/g for HBU680, HBU888, and HBU889, respectively. The HBU888 shows the highest specific capacitance due to the fast PhQ-PhQH2 redox transition at a scan rate of 100 mV/s. The composite electrodes also show a 100% capacity retention over 10,000 cycles. These results show that the new quinone-based derivates can enhance pseudocapacitive behavior and warrant their use as electrode additives for supercapacitors. Graphical abstract The new quinone-based electrode additives were synthesized and used as additives for supercapacitor electrodes. The electrochemical properties are mainly characterized by PhQ-PhQH2 and Q-QH2 redox transitions. The composite electrodes show specific capacitance of 176 F/g, 262 F/g, and 145 F/g for HBU680, HBU888, and HBU889 respectively. The HBU888 shows the highest specific capacitance due to the fast PhQ-PhQH2 redox. The composite electrodes also show a 100% capacity retention over 5000 cycles.